Characterization and phylogenetic analysis of the complete mitochondrial genome of Neurothemis fulvia (Odonata: Anisoptera: Libellulidae). Issue 2 (1st February 2021) - Peng, Xinyuan; Gao, Yuxia; Song, Xiang; Du, Yimin
Abstract: Neurothemis fulvia is a dragonfly of wet forests and usually perches on fallen logs and shrubs. In this study, we sequenced and analyzed the complete mitochondrial genome (mitogenome) of N. fulvia . This mitogenome was 15, 459 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and 2 ribosomal RNA unit genes (rRNAs). The nucleotide composition of the mitogenome was biased toward A and T, with 70.5% of A + T content (A 38.8%, T 31.7%, C 16.6%, and G 12.9%). Gene order was conserved and identical to most other previously sequenced Libellulidae dragonflies. Most PCGs of N. fulvia have the conventional start codons ATN (six ATG, three ATT, and two ATC), with the exception of cox1 and nad1 (TTG). Except for four PCGs ( cox1, cox2, cox3, and nad5 ) end with the incomplete stop codon T––, all other PCGs terminated with the stop codon TAA or TAG. Phylogenetic analysis showed that N. fulvia got together with Tramea virginia with high support value. Libellulidae had a close relationship with Corduliidae, the relationships (( Hydrobasileus + Brachythemis ) + ( Orthetrum + ( Acisoma + ( Neurothemis + Tramea )))) were supported in Libellulidae.